Perlindungan Konsumen Terhadap Overclaim Produk Skincare di Era Digital: Tinjauan Etika Bisnis dan Hukum Positif - Rasmia Agustine Rahmawanty; Halimah Azahrah; Yolanda Maharani; Aldi Misbahul Maad (INDO PUBLISHING, 2025)
The rapid growth of the skincare industry in Indonesia has contributed to the increasing prevalence of overclaim practices, namely exaggerated claims about product benefits that lack scientific justification. The rise of digital media has further amplified this issue, as promotional content can now spread rapidly and on a massive scale. This study aims to examine the consumer protection mechanisms against overclaims in skincare products through a normative approach that combines the analysis of positive law with the principles of business ethics. Employing a qualitative method based on literature review, the findings reveal that overclaim practices not only violate existing consumer protection regulations but also neglect the moral obligations of businesses to uphold transparency and honesty. The study highlights the need to strengthen regulations on digital advertising, clarify the legal responsibilities of influencers, and promote continuous education to foster ethical business conduct and critical consumer awareness.